From Google Searches to Russian Disinformation: Adolescent Critical Race Digital Literacy Needs and Skills - Tynes, Brendesha; Stewart, Ashley; Hamilton, Matthew; Willis, Henry (International Journal of Multicultural Education, 2021)
This study uses a Critical Race Digital Literacy framework to examine Black and Latinx adolescents’ ability to critically evaluate race-related materials online. Participants completed four tasks that required them to engage with a range of race-related material, from search results to social media content. Findings indicate that the majority of participants demonstrated an “emerging” or “mastery” level understanding of search results and determining the trustworthiness of websites. Participants found evaluating the credibility of Twitter content as well as evaluating a Russian disinformation campaign’s Facebook profile targeting African Americans considerably more challenging. In addition, though 34% recognized a video screenshot arguing that building a wall at the southern border is humane as racist, participants had difficulty combining this knowledge with an understanding of online propaganda. Few participants reached mastery on this task, and others that required them to evaluate social media content and recognize disinformation. As more online content and media are explicitly related to race or references specific racial groups, these findings highlight the need for more interventions to enhance competencies around critically evaluating race-related materials online.